Läusestammkulturen an Potentilla anserina (Homoptera: Aphididae). - Domes, Rüdiger (Contributions to Entomology = Beiträge zur Entomologie, 1957)
On Potentilla anserina meet with good conditions of development: Passerinia fragaefolii (Cock)., Passerinia potentillae (Walk.), Dysaulacorthum vincae (Walk.) with 20-29°C, and Rhopalomyzus ascalonicus (Done.) with 15-20°C. Still sufficient are the conditions for Medoralis idaei (v. d. Goot), Myzus ornatus (Laing), and Cerosipha jorbesi (Weed) with 20-25°C, while Nectarosiphon idaei (Börner) badly increases on Potentilla anserina.